Aplikasi Gaya Desain Zen pada Perancangan Interior Body Care di Surabaya - Juventa Nerissa Hartanto; Sriti Mayang Sari (Intra, 2013)
Zen is one of school Mahayana Buddhism which means meditation. The main purpose of zen is a focus on meditation to achieve satori which means enlightenment. Zen concept was chosen to design body care because this concept can support activities such as spa relaxation and reflexology. Zen design style is a simple style that produces coolness, using spontaneous simplicity of the material. Zen design styles are applied through the interior of the body care aims to create an antidote to the stress and tension of everyday life. Expected by the application of the concept of zen on the interior of body care, the people of Surabaya who want to relax can obtain satori experience which feeling relaxed after a treatment.